Spatial evaluation of air quality by biomonitoring of toxic element accumulation in lichens in urban green areas and nature parks on the Anatolian side of Istanbul - ÇOBANOĞLU, GÜLŞAH (My University, 2023)
The city of Istanbul is constantly exposed to air pollution due to its high population, heavy traffic — sea and air transport — and urban industry. This study basically aims to determine the recent level of airborne heavy metals, using lichen biomonitoring method. The cosmopolitan foliose lichen Xanthoria parietina growing abundantly on trees was sampled from 16 urban green spaces in 8 districts on the Anatolian side of Istanbul. Multi-element analysis by ICP-MS was applied to measure the accumulation of 10 potentially toxic trace elements in lichen samples. Spatial distributions of element levels in the air in the sampling areas are shown by mapping. According to the analysis data, the sequence of element deposition levels in lichen samples was as follows; Al > Fe > Mn > Zn > Cr > Cu > Pb > V > Ni > As. Most of the measured atmospheric element amounts yielded results much higher than the reference material in all areas. It was detected that the highest pollution in terms of Al, Cu, Fe, Mn, and Ni elements was in Elmasburnu Nature Park area in Beykoz district, which is a touristic place by the sea. Changes in the city’s air quality over the years have been evaluated by comparing element levels in these locations in a previous biomonitoring study and some differences were found. The resulting data is valuable for periodic monitoring of toxic elements in the air, for determining causes of air pollution, and for taking precautions.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Mühendislik ve Teknoloji; Social Sciences and Humanities; Sociology; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Sosyal Bilimler (SOC); Mühendislik; Sosyal Bilimler Genel; MÜHENDİSLİK, ÇEVRE; ÇEVRE ÇALIŞMALARI; Engineering, Computing & Technology (ENG); Social Sciences (SOC); ENGINEERING; SOCIAL SCIENCES, GENERAL; ENGINEERING, ENVIRONMENTAL; ENVIRONMENTAL STUDIES; Genel Mühendislik; Fizik Bilimleri; Kirlilik; Yönetim, İzleme, Politika ve Hukuk; General Engineering; Physical Sciences; Pollution; Management, Monitoring, Policy and Law; Air quality; Bioaccumulation; Elements; Heavy metals; Lichen monitoring